Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jpn.13544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low‐nutrient‐density diet with probiotic mixture (Bacillus subtilis ms1, B. licheniformis SF5‐1, and Saccharomyces cerevisiae) supplementation on performance of weaner pigs

Abstract: A total of one hundred and forty, 28 day‐old weaner pigs [Duroc × (Yorkshire × Landrace)] with an initial body weight (BW) of 6.56 ± 1.25 kg were used in a six‐week treatment (7 replicate pens per treatment; barrows, and 2 gilts/pen) to evaluate the effect of low‐nutrient‐density diet supplement with probiotic mixture supplementation on the growth performance, nutrient digestibility, faecal microbial and gas emission of weaner pigs. Pigs fed low‐density diet with probiotic mixture supplementation had linearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, LDB induced a significant increase in Lactobacillus abundance and a significant decrease in the abundance of Treponema_2 and Prevotellaceae_NK3B31_group in the top ten most abundant genera. Similar to the results obtained by Sampath et al [57] and Pupa et al [14], Lactobacillus abundance was increased in pigs fed an LDB-supplement diet in our study. Probiotic supplementation inhibits Treponema_2 in pig caecal digesta [12].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, LDB induced a significant increase in Lactobacillus abundance and a significant decrease in the abundance of Treponema_2 and Prevotellaceae_NK3B31_group in the top ten most abundant genera. Similar to the results obtained by Sampath et al [57] and Pupa et al [14], Lactobacillus abundance was increased in pigs fed an LDB-supplement diet in our study. Probiotic supplementation inhibits Treponema_2 in pig caecal digesta [12].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Novotni-Dankó et al (2015) and De Greeff et al (2016) stated that the administration of SM increased body weight and reduced pre-weaning mortality in piglets, respectively. Concurrently, a nutritional approach to the use of probiotics has gained more attention since the 1970's (Fuller, 1977), and this finding was corroborated by many researchers (Nguyen et al, 2019;Sampath et al, 2022) who suggested that a probiotic live microorganism used as a therapeutic adjuvant could improve the feeding behavior and reduce the morbidity and mortality of animals. Such probiotics were recently used in different strains with different efficacies; some of them were established to provide certain benefits to the host (Patil et al, 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Although daily gain showed improvements in pigs fed a 0.05% probiotics supplement, the BW, daily feed intake and gain/feed were unaffected over 6 weeks was constant with Mun et al [ 45 ] who found same result in weaning pigs fed diet supplemented with 0.01% Bacillus subtilis and Bacillus licheniformis probiotics. While, Sampath et al [ 46 ] study reveals that dietary Bacillus licheniformis and Bacillus subtilis has significantly improved the growth performance of weaning pigs. The discrepancies result from the above-mentioned studies made us to hypothesized that age of pigs, species, and strain is also a considerable fact to relate the efficacy of probiotics as they are very active in animals during microbiome development and/or when microbiome stability is compromised.…”
Section: Discussionmentioning
confidence: 99%